2018
DOI: 10.5114/aic.2018.74352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicorandil administration on myocardial microcirculation during primary percutaneous coronary intervention in patients with acute myocardial infarction

Abstract: IntroductionPrevention of the no-reflow phenomenon has a crucial role in primary percutaneous coronary intervention (P-PCI) procedures.AimTo assess the effects of early intracoronary administration of nicorandil (NIC) during P-PCI on myocardial microcirculation in patients with acute myocardial infarction (AMI).Material and methodsA total of 120 patients with first acute anterior wall ST segment elevation myocardial infarction who underwent P-PCI were randomly divided into two groups: the NIC group (A, n = 60)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…This finding is in contrary to those found in the most of previous studies where the drug was used through either intravenous or intracoronary route. [6][7][8][9]13,14 Also, in the present study, oral nicorandil did not have any effect on infarct size reduction and left ventricular function as evident by similar peak cardiac troponin and left ventricular ejection fraction (Table 1) . These findings are consistent with those reported by Kitakaze et al, who showed the intravenous nicorandil with no effect on either infarct size or left ventricular function.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This finding is in contrary to those found in the most of previous studies where the drug was used through either intravenous or intracoronary route. [6][7][8][9]13,14 Also, in the present study, oral nicorandil did not have any effect on infarct size reduction and left ventricular function as evident by similar peak cardiac troponin and left ventricular ejection fraction (Table 1) . These findings are consistent with those reported by Kitakaze et al, who showed the intravenous nicorandil with no effect on either infarct size or left ventricular function.…”
Section: Discussionsupporting
confidence: 60%
“…5 Previous studies have shown that intravenous or intracoronary nicorandil may have cardioprotective effects and may lead to increased myocardial salvage in patients with STEMI undergoing mechanical reperfusion. [6][7][8][9][10] However, in a majority of previous studies, nicorandil has been administered either intravenously or intracoronary, and there is paucity of data on possible cardioprotective effect of oral nicorandil before primary coronary angioplasty. 11,12 Therefore, in the present study, we aimed to assess cardioprotective effect of oral nicorandil during primary angioplasty in patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…The current guidelines of ESC, however, permit the application of IIb/IIIa inhibitors as bailout therapy in the case of large thrombus, slow-or no-reflow, and other thrombotic complications [27]. Furthermore, a recently published study demonstrated the beneficial effect of early intracoronary administration of nicorandil on microcirculation damage [32]. Other strategies aimed at reduction of reperfusion injury, including cyclosporine, which activates mitochondrial potassium channels, failed to improve clinical outcomes and prevent LV remodeling [33], despite previous experimental studies indicating its beneficial effects on infarct size and microvascular obstruction [34].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we are confused about the study by Feng et al We found that they publish another report of the same trial (both are registered in the clinicaltrial.gov, the trial registration number was NCT02435797) 5. However, in that report the total number of included patients was 120; thus, the number was 170 in another report.…”
Section: Dear Editormentioning
confidence: 97%